Rapid fabrication and interface structure of highly faceted epitaxial Ni-Au solid solution nanoparticles on sapphire. (November 2021) - Herre, Patrick; Will, Johannes; Dierner, Martin; Wang, Dong; Yokosawa, Tadahiro; Zech, Tobias; Wu, Mingjian; Przybilla, Thomas; Romeis, Stefan; Unruh, Tobias; Peukert, Wolfgang; Spiecker, Erdmann
Abstract: Supersaturated Ni-Au solid solution particles were synthesized by rapid solid-state dewetting of bilayer thin films deposited onto c -plane sapphire single-crystals. Rapid thermal annealing above the miscibility gap of the Ni-Au system followed by quenching to room temperature resulted in textured and faceted submicron-sized particles as a function of alloying content in the range of 0–28 at% Au. Morphologically, the observed kinetic crystal shapes are confined by close-packed planes; in addition, high-index facets are identified as a function of alloying content by TEM cross-sectioning and equilibrium crystal shape simulations. All samples exhibit a distinct 〈111〉 out-of-plane as well as in-plane texture along densely packed directions. Lattice parameters extracted from independent orthogonal X-ray and electron diffraction techniques prove the formation of a solid solution without tetragonal distortion imposed by the sapphire substrate. At the particle-substrate interface of highly alloyed particles segregation of Au atoms as well as dislocations in stand-off position are found. These observations are in-line with a semi-coherent interface, where Au segregation is triggered by the reduction of the overall strain energy due to: (i) a lower shear modulus on the particle side of the interface, (ii) the shifting of misfit dislocations in stand-off position further away from the stiffer substrate and (iii) a reduction of intrinsic misfit dislocation strain energy on the tensile side. In addition, the mechanical properties of pure and alloyed particles were characterized by in situ compression experiments in the SEM. Typical force-displacement data of defect-free single-crystals were obtained, reaching the theoretical strength of Ni for particles smaller than 400 nm. Alloying changes the mechanical response from an intermittent and discrete plastic flow behavior into a homogeneous deformation regime at large compressive strain. Graphical abstract: Image, graphical abstract